Analysis of the Strength of Evidence of Witness a De-Charge Against the Judge's Decision Regarding the Release of the Defendant in a Tax Crime (Study of Decision Number 97/Pid.Sus/2023/PN Pdg) - Musta, Arif Paria; Yulinda, Kiki; Gantika, Naldi (LPPM Universitas Ekasakti, 2024)
This research examines the strategic significance of defense witnesses in impacting judicial rulings in cases of tax offenses, as illustrated in Decision Number 97/Pid Sus/2023/PN Pdg. A defense witness is a witness enlisted by the accused to undermine or challenge the allegations put forth by the prosecution to lessen or acquit the accused from legal liabilities. In this particular instance, the defense witness delivered pivotal testimony indicating that a third party had settled the tax in question unbeknownst to the defendant. Such testimony played a critical role in the judicial deliberations, convincing the judge to establish that the essential requirements of the charges were not fulfilled, resulting in the defendant's total clearance. This examination reveals that the testimonial influence of defense witnesses carries substantial weight in the adjudicatory process, particularly in intricate scenarios like tax offenses, where robust and credible evidence holds utmost importance. The ruling of the judge to clear the accused stemmed from the non-fulfillment of the requisites causing financial loss to the state, as stipulated in Article 191 Paragraph (2) of the Criminal Procedure Code. Hence, the findings of this research affirm the vital and strategic function of defense witnesses in shaping the ultimate resolution of a criminal lawsuit, especially within tax legislation necessitating thorough and impartial scrutiny of evidence.